1993
DOI: 10.1021/tx00031a009
|View full text |Cite
|
Sign up to set email alerts
|

Base-sequence dependence of covalent binding of benzo[a]pyrenediol epoxide to guanine in oligodeoxyribonucleotides

Abstract: The base-sequence dependence of the yield of the covalent binding reaction of (+)-anti-7 beta, 8 alpha-dihydroxy-9 alpha, 10 alpha-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene [(+)-anti-BPDE] with the exocyclic amino group of guanine surrounded by different flanking bases X and Y in the single-stranded oligonucleotide d(CTATXGYTATC) was investigated. With an initial ratio of [(+)-anti-BPDE]/[oligonucleotide strand] = 2, the percentage of modified strands varied from 20 +/- 2% when the modified dG was surrounded by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
43
1
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 32 publications
6
43
1
1
Order By: Relevance
“…There was a preference for binding to the guanine bases of codon 12 (GGA) over many of the other guanines present. In a study of the reaction of (+) -anti-BPDE with single-stranded oligodeoxyribonucleotides, Margulis et al (33) found higher reactivity for dGs surrounded by pyrimidines than for dGs surrounded by purines, a result consistent with our finding of highest reactivity for CGC in double-stranded oligodeoxyribonucleotides. As in the present study, Osborne (16) found that deoxyguanosines that had a neighboring dG reacted more extensively than dGs that did not (16).…”
Section: Discussionsupporting
confidence: 91%
“…There was a preference for binding to the guanine bases of codon 12 (GGA) over many of the other guanines present. In a study of the reaction of (+) -anti-BPDE with single-stranded oligodeoxyribonucleotides, Margulis et al (33) found higher reactivity for dGs surrounded by pyrimidines than for dGs surrounded by purines, a result consistent with our finding of highest reactivity for CGC in double-stranded oligodeoxyribonucleotides. As in the present study, Osborne (16) found that deoxyguanosines that had a neighboring dG reacted more extensively than dGs that did not (16).…”
Section: Discussionsupporting
confidence: 91%
“… 64 Jernstroem, et al suggest that guanines adjacent to or flanked by guanines are more reactive 62 – 66 In contradiction, other studies predict that guanines flanked by pyrimidine bases are more reactive due to less steric effects as compared to guanines flanked by purine bases. 56 , 67 69 The reactive site of codon 248 in our 32 bp fragment is a guanine flanked by guanine, while codons 244 and 243 are guanines flanked by purine on one side and pyrimidine on the other side and show intermediate reactivity. Codon adduction sites in ss-DNA oligonucleotides are guanines sandwiched between one purine and one pyrimidine.…”
Section: Discussionmentioning
confidence: 90%
“…The sequence of the DNA target plays a role in determining the extent of diol epoxide adduct formation in DNA (Boles & Hogan, 1985;Reardon et al, 1989;Kootstra et al, 1989;Rill & Marsch, 1990;Dittrich & Krugh, 1991a,b;Ross et al, 1993;Margulis et al, 1993;Schwartz et al, 1994). The next question is whether sequence affects the types of adducts that are formed, which themselves may have different biological effects.…”
mentioning
confidence: 99%